2014
DOI: 10.1080/15257770.2014.891741
|View full text |Cite
|
Sign up to set email alerts
|

miR-211 Modulates Gemcitabine Activity Through Downregulation of Ribonucleotide Reductase and Inhibits the Invasive Behavior of Pancreatic Cancer Cells

Abstract: Only a subset of radically-resected pancreatic ductal adenocarcinoma (PDAC) patients benefit from gemcitabine-based chemotherapy, thus the identification of novel prognostic factors is essential. In a high-throughput, microRNA (miRNA) array, miR-211 emerged as the best discriminating miRNA, with high expression associated with long survival. Here, we further explored the biological role of miRNA-211 in gemcitabine activity in the human PDAC cells (SUIT-2) subclones SUIT2-007 and SUIT2-028. Our results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…Several studies have investigated the effect of miR-211 expression on tumorigenesis [10][11][12][13][14][15][16][17][18][19]. Our results are in line with previous findings showing that miR-211 may function as an oncogene [10][11][12].…”
Section: Discussionsupporting
confidence: 96%
See 3 more Smart Citations
“…Several studies have investigated the effect of miR-211 expression on tumorigenesis [10][11][12][13][14][15][16][17][18][19]. Our results are in line with previous findings showing that miR-211 may function as an oncogene [10][11][12].…”
Section: Discussionsupporting
confidence: 96%
“…Moreover, Chu et al [12] indicated that miR-211 could facilitate head and neck squamous cell carcinoma (HNSCC) progression via the inhibition of transforming growth factor-β type II receptor (TGFβRII), disrupted Smad3 phosphorylation, and upregulated c-Myc expression. In contrast with these studies, some authors have reported opposite findings [13][14][15][16][17][18][19]. For example, previous researches were reported that in melanoma cells, overexpression of miR-211 could act as a tumor suppressor miRNA by inhibiting metastasis and invasion through regulation of oncogenes [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Trpm1 is a target gene of microphthalmia-associated transcription factor (MITF) [31,[36][37][38]. It has also been demonstrated that miR-211 can impact cell invasion, proliferation, and migration in many cancers [28][29][30].…”
Section: Discussionmentioning
confidence: 98%